2013
DOI: 10.3109/02699052.2013.766926
|View full text |Cite
|
Sign up to set email alerts
|

Specific attention disorders in drivers with traumatic brain injury

Abstract: These difficulties may have a negative impact on real driving situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…TBI patients only showed a disproportionate increase in reaction times (RTs) under the dual-task condition. All these results considered, DA should be one of the main targets in the rehabilitation of TBI patients, given its key role in many tasks of everyday life (Toyokura et al, 2012 ; Masson et al, 2013 ). However, few rehabilitation programs have been developed to improve this function in patients with TBI [(Couillet et al, 2010 ) specifically addressed DA; (Serino et al, 2007 ; Montani et al, 2014 ) included it in their training programs].…”
Section: Introductionmentioning
confidence: 99%
“…TBI patients only showed a disproportionate increase in reaction times (RTs) under the dual-task condition. All these results considered, DA should be one of the main targets in the rehabilitation of TBI patients, given its key role in many tasks of everyday life (Toyokura et al, 2012 ; Masson et al, 2013 ). However, few rehabilitation programs have been developed to improve this function in patients with TBI [(Couillet et al, 2010 ) specifically addressed DA; (Serino et al, 2007 ; Montani et al, 2014 ) included it in their training programs].…”
Section: Introductionmentioning
confidence: 99%
“…Masson and colleagues documented the negative impact of an increased attentional load on the performance of drivers with TBI (Masson et al, 2013). Conversely, it has been shown that an increase in cognitive workload is associated with a decrease in the variability of lateral position (i.e., better vehicle control) in healthy individuals (Cooper, Medeiros-Ward, & Strayer, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Overload and depletion of attentional resources, as well as sustaining attention on task (Hahn et al, 2012) already reported as being impaired in patients with schizophrenia (Birkett, Brindley, Norman, Harrison, & Baddeley, 2006;Michael et al, 2014), can be detected even in a short task with high attention demands. Although depletion of resources has already been reported in TBI patients (Azouvi et al, 2004;Cossa & Fabiani, 1999;Masson et al, 2013;Zoccolotti et al, 2000), a recent investigation showed that the degree of such impairment is not the same in the two populations ). An alternative interpretation would be that, as the time passes, the degrading effects of noise produced by distractors would accumulate.…”
Section: Instant Overloadmentioning
confidence: 91%
“…There is also evidence that pro-saccades are intact (Heitger et al, 2004), although Kraus et al (2007) showed this to be the case only in mild brain injury. By contrast, deficits of focused attention are frequently reported (Cossa & Fabiani, 1999;Masson et al, 2013;Schmitter-Edgecombe & Kibby, 1998;Zoccolotti et al, 2000). Behavioral and electrocortical evidence suggests there are early target discrimination disturbances in TBI patients (Heinze et al, 1992;Mattson et al, 1994), which contribute to impaired search processes.…”
Section: Differential Processing Of Targets and Distractorsmentioning
confidence: 99%